Cyclo - Rossignon, Christophe; Trần, Anh Hùng 1962-; Lê, Văn Loc; Leung, Tony Chiu Wai 1962-; Trần, Nữ Yên Khê 1968- (Dreamix, 2004)
In the heart of Ho Chi Minh City, a young cyclo (pedicab driver) transports anonymous passengers through the teeming streets, trying to eke out a meager living for his two sisters and elderly grandfather
Orig.: Vietnam, 1995. - Sprache: Vietnames. - Untertitel: Korean., engl. - Special features: cast & staff ; theatrical trailer ; photo gallery
Cinematography by Benoît Delhomme ; edited by Nicole Dedieu and Claude Ronzeau ; music, Ton That Tiet
Keywords: Pedicab drivers / Vietnam / Drama; Families / Vietnam / Drama; Video recordings; Vietnamese language materials; Families; Pedicab drivers; Vietnam